The effects of chlorination, thickness, and moisture on glove donning efficiency. Issue 9 (2nd September 2021) - Preece, Daniel; Hong Ng, Thian; Tong, Heam Kit; Lewis, Roger; Carré, Matt J.
Abstract: Changing gloves more frequently is encouraged, more now than ever given the COVID-19 pandemic. When the donning process has moisture introduced, however, complications can arise, which consumes vital time. Most commonly, gloves undergo a chlorination treatment to reduce glove tack, allowing easier donning. To assess the effects of different chlorination strengths and glove thicknesses on donning, acrylonitrile butadiene gloves were manufactured at two different thicknesses (0.05 and 0.10 mm) with 4 different chlorination treatments: 0, 500, 1000 and 2000 ppm. Six participants were used to assess the time taken to don each of the glove sets with dry and wet hands (16 tests in total). Overall, the thicker gloves took longer to don, due to differences in the material stiffness hindering the donning process. The quickest performance from the chlorinated gloves was noted in the 1000 and 2000 ppm concentrations. Wet conditions also showed significant increases in the donning time. Practitioners Summary: The study was conducted based on the gaps identified in previous literature reviews which revealed the requirement for a greater understanding of glove donning process. It was found a stronger chlorination was detrimental when the hands were wet, but better when dry. Thicker gloves were also found to be detrimental. Abbreviations: PPE: personal protective equipment; NBR: acrylonitrile butadiene rubber; NRL: natural rubber latex; EN: European standards; s: seconds; Ts: tensile strength; Fb: force at break; T: thickness; Eb: elongation at break; HSD: honest significant difference; FTIR: Fourier transform infrared; covid-19: coronavirus disease 2019